A taxonomic study of the genus Macromotettix Günther (Orthoptera: Tetrigoidea: Metrodoridae) - Deng, Weian; Zheng, Zhemin; Wei, Shizhen (Zootaxa, 2007)
Sixteen species of Macromotettix Günther were systematically researched in this paper. One species, Macromotettix guangxiensis sp.nov., is described as new to science. An updated key to the species of Macromotettix is presented. The type specimens are deposited in the Institute of Zoology, Shaanxi Normal University, Xi’an, China (5%4&) and Department of Chemistry and Life Science, Hechi University, China (6%10&).